Natural Resources Endowment, Institutional Quality and External Debt in Selected African Countries - Akomolafe, K. J. (African Journal of Stability and Development (AJSD), 2024)
This study examines the effects of natural resources endowment and institutional quality on external debt in selected nine African countries from 1996 to 2019. Two measures of institutional quality, control of corruption and government effectiveness, were used as measures of institutional quality while feasible generalized least square (FGLS) was used for the estimation. The findings suggest that natural resources rent leads to more external debts, but control of corruption and government effectiveness reduce it. However, moderating natural resource rent with control of corruption and government effectiveness does not entirely mitigate the positive effect of natural resources on external debt. It is therefore recommended that African governments should not rely solely on enhancing institutional quality as means to reducing foreign debt, but should embrace a more thorough and multifaceted strategy that involves enhancing debt management, economic diversification, fiscal discipline, and resource revenue management.